Function of CSF1 and IL34 in Macrophage Homeostasis, Inflammation, and Cancer - Lin, WeiYu; Xu, Daqi; Austin, Cary D.; Caplazi, Patrick; Senger, Kate; Sun, Yonglian; Jeet, Surinder; Young, Judy; Delarosa, Donnie; Suto, Eric; Huang, Zhiyu; Zhang, Juan; et al. (Frontiers in Immunology, 2019)
Colony stimulating factor 1 (CSF1) and interleukin 34 (IL34) signal via the CSF1 receptor to regulate macrophage differentiation. Studies in IL34- or CSF1-deficient mice have revealed that IL34 function is limited to the central nervous system and skin during development. However, the roles of IL34 and CSF1 at homeostasis or in the context of inflammatory diseases or cancer in wild-type mice have not been clarified in vivo. By neutralizing CSF1 and/or IL34 in adult mice, we identified that they play important roles in macrophage differentiation, specifically in steady state microglia, Langerhans cells and kidney macrophages. In several inflammatory models, neutralization of both CSF1 and IL34 contributed to maximal disease protection. However, in a myeloid cell-rich tumor model, CSF1 but not IL34, was required for tumor-associated macrophage accumulation and immune homeostasis. Analysis of human inflammatory conditions reveals IL34 upregulation that may account for the protection requirement of IL34 blockade. Furthermore, evaluation of IL34 and CSF1 blockade treatment during Listeria infection reveal no substantial safety concerns. Thus, IL34 and CSF1 play non-redundant roles in macrophage differentiation, and therapeutic intervention targeting IL34 and/or CSF1 may provide an effective treatment in macrophage driven immune-pathologies.